Development of a New Combination Compound (Cyclopamine) Isolated from Veratrum californicum and 5-FU Acting as Anti-invasive and Initiator of Intrinsic Apoptosis Mechanism against Aggressive Type Colorectal Cancer Cells - Manmuan, Suwisit; Tubtimsri, Sukannika; Manmuan, Ponwit (Trends in Sciences, 2022)
Characteristics of programmed cell death are generally regarded as defined by cell outgrowth or cellular aging and distinct morphological characteristics featuring nuclear condensation and formation of apoptotic bodies. Apoptosis is considered to have a function at cellular level and is essential to long-lived cell differentiation undergoing senescence and apoptosis. Inappropriate apoptosis is a factor that results in serious conditions, causing multiple disease progression as well as cancer. The ability to modulate the life or death of a cancer cell is recognized for its immense therapeutic potential. Therefore, the research findings that are focused on the elucidation of a newly synthesized drug or drug derived from a natural plant to stop the cell cycle mechanism and signaling pathways that control cell cycle arrest and apoptosis are considered necessary. The field research of apoptosis is moving forward at a rapid rate. The goal of this paper is to investigate a natural active constituent, which is simply identified as “a drug for near future co-chemotherapy”, as well as to explore the ability to activate the apoptotic pathway. Our results demonstrated that cyclopamine provides an excellent anti-tumor activity and changing of the morphology of cancerous cells in the early and late phases of apoptosis, indicating that cyclopamine has the potential to chemosensitize SW-620 cancer cells to 5-FU based chemotherapy, which may be useful for the treatment of colorectal cancer and the fight to overcome drug resistance in advanced colorectal cancer.